Pharmacological targeting of gastric mucosal barrier with traditional Chinese medications for repairing gastric mucosal injury - Jia, Xueyan; He, Yihuai; Li, Lin; Xu, Delin (Frontiers in Pharmacology, 2023)
Abstract: The gastric mucosa (GM) is the first barrier and vital interface in the stomach that protects the host from hydrochloric acid in gastric juice and defends against exogenous insults to gastric tissues. The use of traditional Chinese medications (TCMs) for the treatment of gastric mucosal injury (GMI) has long-standing history and a good curative effect. Whereas there are poor overall reports on the intrinsic mechanisms of these TCM preparations that pharmacology uses to protect body from GMI, which is crucial to treating this disease. These existing reviews have deficiencies that limit the clinical application and development of both customary prescriptions and new drugs. Further basic and translational studies must be done to elucidate the intrinsic mechanisms of influence of these TCM preparations. Moreover, well-designed and well-conducted experiences and clinical trials are necessary to ascertain the efficacy and mechanisms of these agents. Therefore, this paper presents a focused overview of currently published literature to assess how TCMs action that facilitates the cures for GMI. It offers a whole train of current state of pharmacological evidence, identifies the pharmacological mechanisms of TCMs on GM, and highlights that remarkable capacity of TCMs to restore GM after damage. These TCM preparations promote the repair of multicomponent targets such as the gastric mucus, epithelial layer, blood flow (GMBF) and lamina propria barrier. Overall, this study has summarized the essential regulatory mechanisms and pharmacological efficacy of TCMs on new and productive therapeutic targets. This review provides an avenue for studying various drugs with potentially promising effects on mucosal integrity, as well as subsequent pharmacological studies, clinical applications and new drug development.